Pendampingan Pengelolaan Sampah Berbasis Masyarakat di Desa Kenjo Banyuwangi - Musyarofah, Atiqatul; Sudarsri Lestari; Mufidah Yusroh; Anis Hidayati MS; Nurul Fatimah (STAI Ma'had Aly Al-Hikam Malang, 2025)
Abstract A clean environment is not only beneficial for health, but also reflects a family's adequate and sustainable access to income and resources to meet its basic needs, such as food, clean water, public services, education, housing, community participation, and social integrity. This healthy environment awareness activity is very important in fostering motivation within the community, especially within families. Therefore, more intensive and relatively long-term guidance is needed to ensure the assistance is more effective. The community service students (KKN) have taken steps to address this issue. Their efforts include organizing awareness campaigns on healthy environments and waste management, encouraging the community to maintain cleanliness by conducting regular